2010
DOI: 10.1038/nature08671
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for the photoconversion of a phytochrome to the activated Pfr form

Abstract: Phytochromes are a collection of bilin-containing photoreceptors that regulate numerous photoresponses in plants and microorganisms through their ability to photointerconvert between a red light-absorbing, ground state Pr and a far-red light-absorbing, photoactivated state Pfr1,2. While the structures of several phytochromes as Pr have been determined3-7, little is known about the structure of Pfr and how it initiates signaling. Here, we describe the three-dimensional solution structure of the bilin-binding do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
168
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(192 citation statements)
references
References 45 publications
7
168
4
Order By: Relevance
“…E, and F vs. G) exhibit entirely different 1 H correlations, providing clear evidence that the Pr → Pfr phototransformation is associated with Z-to-E isomerization at the C15═C16 methine bridge (Datasets S3 and S4). Our data thus refute the idea that a photoisomerization between rings A-B constitutes the photoactivation mechanism in all phytochromes (23). The lack of the PHY domain in the SyB-Cph1 (GAF) fragment (23) might explain the apparent discrepancy in the primary motion of the chromophore during photoconversion.…”
Section: Resultscontrasting
confidence: 49%
See 1 more Smart Citation
“…E, and F vs. G) exhibit entirely different 1 H correlations, providing clear evidence that the Pr → Pfr phototransformation is associated with Z-to-E isomerization at the C15═C16 methine bridge (Datasets S3 and S4). Our data thus refute the idea that a photoisomerization between rings A-B constitutes the photoactivation mechanism in all phytochromes (23). The lack of the PHY domain in the SyB-Cph1 (GAF) fragment (23) might explain the apparent discrepancy in the primary motion of the chromophore during photoconversion.…”
Section: Resultscontrasting
confidence: 49%
“…1 B vs. C). Very recently, however, Ulijasz et al presented structural simulations based on liquid NMR data of a 20-kDa GAF (cGMP phosphodiesterase/ adenylyl cyclase/FhlA) domain fragment of "SyB-Cph1" phytochrome from the thermotolerant cyanobacterium Synechococcus OSB′ (23). Surprisingly, they concluded that photoisomerization occurs at the methine bridge between rings A-B rather than C-D, proposing the former as a general model for phytochrome activation.…”
mentioning
confidence: 99%
“…Together with Pro 81 of the DIP motif, Pro 382 forms a clamp hindering large conformational changes of the A-ring. Interestingly, earlier NMR studies on the P fr -like state of an isolated GAF domain of another Group II phytochrome postulated A-ring rotation as part of the photocycle (6). Given that this ubiquitous structural restraint in Group I and II phyto- Fig.…”
Section: Table 2 Ring Tilts Of Pcb From X-ray Crystallography and Qm/mentioning
confidence: 99%
“…These alterations ultimately control signal transfer either to effector proteins (inter-molecular (4)) or effector domains like histidine kinase domains (intra-molecular (5)). How these allosteric effects are triggered by D-ring rotation at the molecular level is still unknown thus prompting alternative scenarios for downstream signaling by phytochromes including an additional A-ring rotation upon P r 3 P fr photoconversion (6).…”
mentioning
confidence: 99%
“…Both the branch-site test and the character mapping exercise identify the sequence coordinates of change, and these can be evaluated in the light of crystal structures that have recently been presented (Wagner et al, , 2007Yang et al, 2007Yang et al, , 2008Cornilescu et al, 2008;Essen et al, 2008;Ulijasz et al, 2010) and can be compared with known mutants. Currently, high-resolution structures of the photosensory core of prokaryotic phytochromes are available; this region is homologous with the sensory module of plant phytochromes (Montgomery and Lagarias, 2002;Lamparter, 2004;Karniol et al, 2005) and consists of PAS, GAF, and PHY domains ( Figure 3B).…”
Section: Synthesis Of Functional Evolutionary and Structural Datamentioning
confidence: 99%